2023
DOI: 10.3390/biomedicines11030691
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Functions of Telomerase Reverse Transcriptase in Head and Neck Cancer

Abstract: Head and neck cancers (HNCs) are among the ten leading malignancies worldwide. Despite significant progress in all therapeutic modalities, predictive biomarkers, and targeted therapies for HNCs are limited and the survival rate is unsatisfactory. The importance of telomere maintenance via telomerase reactivation in carcinogenesis has been demonstrated in recent decades. Several mechanisms could activate telomerase reverse transcriptase (TERT), the most common of which is promoter alternation. Two major hotspot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…The therapeutic cancer UV1 consists of three synthetic peptides which cover a sequence within the active catalytic site of hTERT ( 24 ). hTERT promoter mutations which are a common mechanism of hTERT activation are found in the two major hotspots C228T and C250T ( 14 ). In HNSCC hTERT promoter mutations were found to be associated with poorer overall survival in some studies ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic cancer UV1 consists of three synthetic peptides which cover a sequence within the active catalytic site of hTERT ( 24 ). hTERT promoter mutations which are a common mechanism of hTERT activation are found in the two major hotspots C228T and C250T ( 14 ). In HNSCC hTERT promoter mutations were found to be associated with poorer overall survival in some studies ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common mechanism of hTERT activation are mutations in the promoter region of hTERT ( 13 ). In HNSCC frequencies of hTERT promoter mutations vary among different studies ( 14 ). Frequencies up to 64,7% have been reported depending on tumor site, risk factors such as human papillomavirus status and ethnicity ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, non-invasive biomarkers such as tumor oxygenation and signals from autofluorescence imaging, intensity signals from optical coherence tomography, and ultrasound wave signals from surface tumor tissues have been shown to provide accurate predictions for early detection and prognosis assessments in OSCC [30]. To overcome these challenges, this Special Issue has accepted a few publications that highlighted the potential biomarkers that can be used for diagnostic and therapeutic purposes [31][32][33][34][35][36][37][38][39][40]. The diagnostic section can be divided into biomarkers for OSCC and prognosis.…”
Section: Limitations Challenges and Conclusionmentioning
confidence: 99%
“…In this case, studies have demonstrated that the protein expression of C44Mab-34 [32] can solely detect the OSCC cell as opposed to the stroma or immune cell, and the downregulation of IFIT2 has been identified as a poor prognostic marker for OSCC [33]. A review paper conducted by Yeh et al [40] summarized evidence showing that TERT promoter mutations were associated with poor survival in OSCC. Apart from the mutations and protein expression of the markers, this Special Issue also provides evidence of using the clinicopathological parameter (lymph node ratio) as a prognosticator to access patient clinical outcome post surgery [36].…”
Section: Limitations Challenges and Conclusionmentioning
confidence: 99%